High-tensile and high-conductivity hydrogel with layered structure as well as preparation method and application of high-tensile and high-conductivity hydrogel
By introducing PEDOT:PSS nanoparticles and EGaIn micro/nanoparticles into the hydrogel to form a layered structure, the balance between the conductivity and mechanical robustness of the hydrogel is solved, and a highly tensile and highly conductive hydrogel is prepared, which is suitable for flexible electronic devices such as wearable capacitive sensors and bioelectrodes.
Patent Information
- Application Number
- CN202411351898.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing hydrogel materials struggle to balance high conductivity and mechanical robustness. Traditional methods result in structural inhomogeneity or stress concentration, making it difficult to meet the requirements of flexible electronic devices.
Polyvinyl alcohol and PEDOT:PSS were used as monomer solutions, and EGaIn micro-nano particles were added. The hydrogel with a layered structure was formed by ultrasonic dispersion. The PEDOT:PSS nanoparticles and liquid metal particles were electrostatically adsorbed to form a dense conductive layer and enhance mechanical properties.
It achieves high tensile strength and high conductivity. The hydrogel maintains stable resistance at 617% tensile strain. Its Young's modulus and toughness are superior to existing materials. It is suitable for flexible wearable capacitive sensors and bioelectrodes, and has fast response and high sensitivity sensing performance.
Smart Images

Figure CN119286001A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flexible conductive materials and relates to a highly stretchable and highly conductive hydrogel with a layered structure and a preparation method and application thereof. Background Art
[0002] Hydrogels are considered promising candidates for building soft electronic and biomedical devices due to their mechanical flexibility, structural permeability, and biocompatibility. However, most hydrogels are non-conductive, which limits their application in these fields. The research and development of conductive hydrogels has created new possibilities for their applications in advanced technology fields, such as implantable bioelectrodes, soft actuators, and tissue engineering platforms. Despite extensive research, achieving high conductivity and mechanical robustness in hydrogels remains challenging. Traditional ion-conductive hydrogels achieve ion conductivity by introducing electrolytes into the aqueous phase. Due to the Hofmeister effect, this process leads to the densification of the polymer network structure and enhances the mechanical properties of ion-conductive hydrogels by increasing the cross-linking density. However, limited by the solubility of the electrolyte and the low mobility of the ions, ion-conductive hydrogels typically exhibit a mechanical conductivity of 10 S·m -1 The electrical conductivity is about 1.07 W, which is several orders of magnitude lower than that of electronic conductors, greatly limiting the application scope of conductive hydrogels.
[0003] To improve the conductivity of hydrogels, adding electronic conductive components can effectively enhance their conductivity. The traditional method is to add conductive fillers such as metal or carbon fillers to the hydrogel matrix. However, due to the random distribution of conductive fillers in the hydrogel matrix, it is difficult to construct a three-dimensional conductive network at a low content level (e.g. <10wt%). Excessive addition of conductive fillers will destroy the uniformity of the hydrogel structure, leading to stress concentration, which will cause the failure of the conductive hydrogel under small strain. Another way to improve the conductivity of hydrogels is to add conductive polymers, such as poly (3,4-ethylenedioxythiophene) or polyaniline, which can form a fibrous three-dimensional conductive network in the hydrogel, or attach to the original polymer network to construct a three-dimensional conductive network. Compared with adding conductive fillers, the three-dimensional conductive network formed by conductive polymers has better uniformity and mechanical properties, and provides better ductility. However, due to the inherent properties of conductive polymers, the conductivity of related hydrogels is usually limited to 1,000S·m -1 the following.
[0004] Liquid metals (LMs), such as eutectic gallium-indium alloys (EGaIn), have attracted extensive attention in recent years due to their non-toxicity, high thermal and electrical conductivity, large surface tension, low vapor pressure, and low viscosity. Although existing research has made important progress in integrating liquid metals with hydrogels, each material system still needs to make a trade-off between meeting the high conductivity requirements of commercial electronic components and the flexibility and deformability of hydrogels.
[0005] Yan's team prepared IM conductive elastomers by adding ultrasonically treated EGaIn nanoparticles to polyvinyl alcohol (PVA), achieving a 50-fold increase in ductility, but the material's conductivity was poor and could not meet the application requirements of highly conductive devices (Wang X, Zheng S, Xiong J, et al. Stretch-Induced Conductivity Enhancement in Highly Conductive and Tough Hydrogels[J]. Advanced Materials, 2024: 2313845).
[0006] Xuan's team introduced microchannels into PDMS elastomers and achieved reversible circuit conduction through the microchannels between LM droplets. Under small stress, it can be applied to devices such as switches. However, the material has low ductility and fails under large stress, which cannot meet the requirements of wearable devices (He X, Wu J, Xuan S, et al. Stretchable and recyclable liquid metal droplets embedded elastomer composite with high mechanically sensitive conductivity [J]. ACS Applied Materials & Interfaces, 2022, 14 (7): 9597-9607).
[0007] Therefore, developing a simple method to prepare liquid metal-based conductive hydrogels with good mechanical behavior and conductivity has good scientific research significance and application prospects. Summary of the invention
[0008] The object of the present invention is to provide a highly tensile and highly conductive hydrogel with a layered structure, and a preparation method and application thereof. The hydrogel uses polyvinyl alcohol and PEDOT:PSS as monomer solutions, adds EGaIn micro-nano particles after mixing, obtains a mixed solution after ultrasonic dispersion, and then obtains a highly tensile and highly conductive hydrogel with a layered structure after injection molding. PEDOT:PSS nanoparticles have a Zeta potential opposite to that of liquid metal particles, can be adsorbed with liquid metal particles, and promote the deposition of smaller-sized liquid metal particles. The deposited liquid metal forms a dense conductive layer at the bottom, providing excellent conductive properties for the hydrogel. At the same time, the liquid metal nanoparticles dispersed in the PVA hydrogel layer, together with the PEDOT:PSS nanoparticles and the PVA crystal domains, act as crosslinking points to improve the mechanical properties of the material. The hydrogel prepared by the present invention has a typical layered structure, while taking into account good mechanical properties and conductive properties, can meet the use requirements of different scenarios, thereby expanding the working range and application scenarios of flexible electronic devices based on conductive hydrogels.
[0009] The technical solution for achieving the purpose of the present invention is as follows:
[0010] The method for preparing a highly stretchable and highly conductive hydrogel with a layered structure specifically comprises the following steps:
[0011] (1) adding a 1.0% PEDOT:PSS solution to a PVA solution at a mass ratio of 1:1 to 3:1, and then adding water to mix and stir to obtain a monomer solution;
[0012] (2) adding EGaIn micro-nano particles to PVA at a mass ratio of 0.5 to 1.5:1 to the monomer solution, and obtaining a mixed solution after ultrasonic dispersion;
[0013] (3) The mixed solution is injected into a mold, heated and cured at 70±5°C for 30-40 min, and then demolded to obtain a highly stretchable and highly conductive hydrogel with a layered structure.
[0014] Preferably, in step (1), the mass concentration of the PVA solution is 10%, and the mass ratio of the PEDOT:PSS solution to the PVA is 2:1.
[0015] Preferably, in step (1), in the monomer solution, the mass ratio of PVA to water is 0.1:1.494.
[0016] The present invention also provides a highly stretchable and highly conductive hydrogel with a layered structure prepared by the above preparation method.
[0017] Furthermore, the present invention provides the use of the highly stretchable and highly conductive hydrogel with a layered structure in the preparation of a flexible wearable capacitive sensor.
[0018] Preferably, the specific method of the above application is: the hydrogel layers of two sheets of the above-mentioned high-stretchability and high-conductivity hydrogel with a layered structure are brought into contact with each other, the conductive layers of the two hydrogels are used as the upper and lower electrodes of the sensor respectively, and then packaged with VHB tape to prepare a flexible wearable capacitive sensor.
[0019] Furthermore, the present invention provides the use of the highly stretchable and highly conductive hydrogel with a layered structure in the preparation of a bioelectrode.
[0020] The hydrogel prepared by the present invention is a conductive hydrogel with a layered structure, which has a unique composition, with EGaIn micro / nano droplets concentrated on one side and polyvinyl alcohol hydrogel on the other side. In order to achieve high conductivity in the liquid metal conductive layer and prevent liquid metal particles (LMPs) from aggregating in the PVA hydrogel, PEDOT:PSS nanoparticles with a Zeta potential opposite to that of LMPs are introduced. Under the combined action of gravity sedimentation and electrostatic assisted sedimentation, the liquid metal conductive layer forms a network with large liquid metal particles as the main skeleton and small particles as network connectors.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) In order to achieve high conductivity in the liquid metal conductive layer while preventing the liquid metal particles from aggregating in the hydrogel layer, the present invention introduces PEDOT:PSS nanoparticles having an opposite Zeta potential to the liquid metal particles into the hydrogel precursor solution. The introduction of PEDOT:PSS nanoparticles allows electrostatic adsorption on the surface of smaller liquid metal particles, which assists sedimentation by increasing the size of the liquid metal particles.
[0023] (2) Under the combined effects of gravity sedimentation and electrostatic assisted sedimentation, the liquid metal conductive layer forms a network with large liquid metal particles as the main framework, and smaller particles as conductive network interconnectors. This configuration of the liquid metal layer has excellent conductivity (1.67×10 5 S·m -1 ), and maintained a stable resistance under a tensile strain of 617%.
[0024] (3) Due to the presence of multiple cross-linking mechanisms, including PVA crystalline domains, PEDOT:PSS nanoparticles, and liquid metal particles, the prepared conductive hydrogel exhibits high Young’s modulus (~178.14 MPa), stretchability (~818%), and toughness (~185.9 MJ·m -3), outperforming most existing tough gels, biological tissues, and natural rubber.
[0025] (4) The unique layered structure of the hydrogel of the present invention enables the assembled flexible wearable capacitive sensor to have excellent sensing performance. The flexible wearable capacitive sensor is prepared by assembling two sheets of conductive hydrogel with a layered structure, wherein the PVA hydrogel layer can be used as the dielectric layer of the capacitive sensor due to its insulation. Therefore, the PVA hydrogel layers are in contact with each other during the assembly process, and the liquid metal conductive layer serves as the upper and lower electrodes of the capacitive sensor to transmit signals through external wires. This capacitive sensor that does not require additional dielectric layers to assemble has ultra-thin and ultra-fast detection capabilities. During the test, it can accurately and quickly (~20ms) detect the movement of different joints of the human body, and can generate signal responses to objects with a tiny mass of 0.05g.
[0026] (5) The hydrogel of the present invention can also be used to prepare bioelectrodes, which can accurately monitor human body movements and bioelectric signals. For example, it can be attached around the human eye to measure the electrooculogram (EOG) signal, or attached to the human wrist pulse to measure the electrocardiogram (ECG) signal. It has high sensitivity and accuracy and shows great application potential in the fields of soft electronics and wearable technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a structural diagram of a conductive hydrogel having a layered structure;
[0028] Figure 2 is a tensile stress-strain curve diagram of the conductive hydrogel with a layered structure prepared in Examples 1-7;
[0029] Figure 3 is a graph of toughness and elastic modulus of the conductive hydrogels with layered structures prepared in Examples 1-7;
[0030] Figure 4 is a stress-strain curve diagram of the conductive hydrogel with a layered structure prepared in Examples 3, 8-11;
[0031] Figure 5 is a graph of toughness and elastic modulus of the conductive hydrogels with layered structures prepared in Examples 3, 8-11;
[0032] Figure 6 is the initial resistance graph of the conductive hydrogel with a layered structure prepared in Examples 3, 9-11;
[0033] Figure 7 is a tensile resistance graph of the conductive hydrogel with a layered structure prepared in Examples 3, 9-11;
[0034] Figure 8is a graph of the relative rate of change of resistance of the conductive hydrogel with a layered structure prepared in Example 10 under the pressure of a heavy object;
[0035] Fig. 9 is a graph of the relative rate of change of resistance of the conductive hydrogel with a layered structure prepared in Example 10 when bent;
[0036] Fig.10 is a graph of the relative rate of change of resistance of the conductive hydrogel with a layered structure prepared in Example 10 when twisted;
[0037] Fig.11 The capacitance change response curve of the flexible capacitive sensor prepared based on the conductive hydrogel with a layered structure prepared in Example 10 as the finger is bent;
[0038] Fig.12 is a capacitance change response curve of the flexible capacitive sensor prepared based on the conductive hydrogel with a layered structure prepared in Example 10 as the knee is bent;
[0039] Fig.13 is a capacitance change response curve of the flexible capacitive sensor prepared based on the conductive hydrogel with a layered structure prepared in Example 10 in response to swallowing action;
[0040] Fig.14 is a response time curve of a flexible capacitive sensor prepared based on a conductive hydrogel with a layered structure prepared in Example 10 under a single press;
[0041] Fig.15 The capacitance change response curve of the flexible capacitive sensor prepared based on the conductive hydrogel with a layered structure prepared in Example 10 at different pressing times;
[0042] Fig.16 The capacitance change response curve of the flexible capacitive sensor prepared based on the conductive hydrogel with a layered structure prepared in Example 10 under different pressures;
[0043] Fig.17 is an EOG signal test curve of a bioelectrode prepared based on a conductive hydrogel having a layered structure prepared in Example 10;
[0044] Fig.18 This is an ECG signal test curve of the bioelectrode prepared based on the conductive hydrogel with a layered structure prepared in Example 10. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0046] Example 1 Hydrogel PLM 0.5 Preparation
[0047] (1) 1.0 g of PVA was dissolved in 9 g of deionized water at 90° C. to obtain a 10% PVA solution. 0.594 g of deionized water was added to a glass bottle and stirred continuously at 1500 rpm for 30 min to obtain a monomer solution.
[0048] (2) 0.05 g of EGaIn micro-nanoparticles were added to 1.0 g of PVA solution, and a mixed solution was obtained after ultrasonic dispersion.
[0049] (3) The mixed solution is injected into the mold, and after heating and curing at 70±5°C for 30-40 minutes, the mold is removed to obtain the conductive hydrogel PLM. 0.5 .
[0050] Example 2 Highly stretchable and highly conductive hydrogel PPS with layered structure 1 LM 0.5 Preparation
[0051] (1) 1.0 g of PVA was dissolved in 9 g of deionized water at 90° C. to obtain a 10% PVA solution. According to the mass ratio of PEDOT:PSS solution to PVA being 1:1, 1.0 g of PVA solution, 0.1 g of 1% PEDOT:PSS solution and 0.495 g of deionized water were added to a glass bottle under continuous stirring at 1500 rpm for 30 min to obtain a monomer solution.
[0052] (2) 0.05 g of EGaIn micro-nanoparticles were added to the monomer solution, and a mixed solution was obtained after ultrasonic dispersion.
[0053] (3) The mixed solution was injected into a mold, and after being heated and cured at 70±5°C for 30-40 min, the mold was removed to obtain a conductive hydrogel PPS with a layered structure. 1 LM 0.5 .
[0054] Example 3 Highly stretchable and highly conductive hydrogel PPS with layered structure 2 LM 0.5 Preparation
[0055] This embodiment is basically the same as embodiment 2, except that in step (1), the mass ratio of the PEDOT:PSS solution to PVA is 2:1. Specifically, according to the mass ratio of the PEDOT:PSS solution to PVA being 2:1, 1.0 g of PVA solution, 0.2 g of a 1% PEDOT:PSS solution and 0.396 g of deionized water are added to a glass bottle at a speed of 1500 rpm for 30 min, and stirred continuously to obtain a monomer solution.
[0056] Example 4 Highly stretchable and highly conductive hydrogel PPS with layered structure 3 LM 0.5 Preparation
[0057] This embodiment is basically the same as embodiment 2, except that in step (1), the mass ratio of the PEDOT:PSS solution to PVA is 3:1. Specifically, according to the mass ratio of the PEDOT:PSS solution to PVA being 3:1, 1.0 g of PVA solution, 0.3 g of a 1% PEDOT:PSS solution and 0.297 g of deionized water are added to a glass bottle at a speed of 1500 rpm and stirred continuously for 30 min to obtain a monomer solution.
[0058] Example 5 Hydrogel PPS with layered structure 4 LM 0.5 Preparation
[0059] This embodiment is basically the same as embodiment 2, except that in step (1), the mass ratio of the PEDOT:PSS solution to PVA is 4:1. Specifically, according to the mass ratio of the PEDOT:PSS solution to PVA being 4:1, 1.0 g of PVA solution, 0.4 g of a 1% PEDOT:PSS solution and 0.198 g of deionized water are added to a glass bottle at a speed of 1500 rpm for 30 min, and stirred continuously to obtain a monomer solution.
[0060] Example 6 Hydrogel PPS with layered structure 5 LM 0.5 Preparation
[0061] This embodiment is basically the same as embodiment 2, except that in step (1), the mass ratio of the PEDOT:PSS solution to PVA is 5:1. Specifically, according to the mass ratio of the PEDOT:PSS solution to PVA being 5:1, 1.0 g of PVA solution, 0.5 g of a 1% PEDOT:PSS solution and 0.099 g of deionized water are added to a glass bottle at a speed of 1500 rpm and stirred continuously for 30 min to obtain a monomer solution.
[0062] Example 7 Hydrogel PPS with layered structure6 LM 0.5 Preparation
[0063] This embodiment is basically the same as embodiment 2, except that in step (1), the mass ratio of the PEDOT:PSS solution to PVA is 6:1. Specifically, according to the mass ratio of the PEDOT:PSS solution to PVA being 6:1, 1.0 g of PVA solution and 0.6 g of a 1% PEDOT:PSS solution are added to a glass bottle at a speed of 1500 rpm and stirred continuously for 30 min to obtain a monomer solution.
[0064] Mechanical properties testing of conductive hydrogels with hierarchical structures with different monomer ratios
[0065] The mechanical properties of the hydrogels with layered structures obtained in Examples 1 to 7 were tested, and the stress-strain curves thereof are shown in FIG. Figure 2 As shown, the toughness and modulus diagram is as follows Figure 3 As shown. The fracture strain of the conductive hydrogel with a layered structure ranges from 200% to 770%. As the ratio of PEDOT:PSS monomers increases, the fracture strain of the conductive hydrogel with a layered structure decreases, and the toughness first increases and then decreases, but the modulus increases. The reason is that PEDOT:PSS, as a nanofiller, can coordinate with PVA to form cross-linking points. Therefore, as the content of PEDOT:PSS increases, the cross-linking density of PVA increases, and due to the rigid nature of PEDOT:PSS, the ductility of the conductive hydrogel with a layered structure continues to decrease, and the strength continues to increase. When the mass ratio of PEDOT:PSS solution to PVA is 2:1, the conductive hydrogel with a layered structure has the greatest toughness, so this ratio is selected for subsequent testing.
[0066] Example 8 Hydrogel PPS with layered structure 2 LM 0 Preparation
[0067] (1) 1.0 g of PVA was dissolved in 9 g of deionized water at 90° C. to obtain a PVA solution with a concentration of 10%. Based on a mass ratio of PEDOT:PSS solution to PVA of 2:1, 1.0 g of PVA solution, 0.2 g of a 1% PEDOT:PSS solution, and 0.396 g of deionized water were added to a glass bottle under continuous stirring at 1500 rpm for 30 min to obtain a monomer solution.
[0068] (2) The mixed solution is injected into a mold, and after being heated and cured at 70±5° C. for 30 to 40 minutes, the mold is removed to obtain a conductive hydrogel with a layered structure and high mechanical properties.
[0069] Example 9 Highly stretchable and highly conductive hydrogel PPS with layered structure 2 LM 1.0 Preparation
[0070] This embodiment is basically the same as embodiment 3, except that in step (2), the mass ratio of EGaIn micro-nano particles to PVA is 1:1, specifically, 0.1 g of EGaIn micro-nano particles is added to the monomer solution, and a mixed solution is obtained after ultrasonic dispersion.
[0071] Example 10 Highly stretchable and highly conductive hydrogel PPS with layered structure 2 LM 1.5 Preparation
[0072] This embodiment is basically the same as embodiment 3, except that in step (2), the mass ratio of EGaIn micro-nano particles to PVA is 1.5:1, specifically, 0.15 g of EGaIn micro-nano particles are added to the monomer solution, and a mixed solution is obtained after ultrasonic dispersion.
[0073] Example 11 Hydrogel PPS with layered structure 2 LM 2 Preparation
[0074] This embodiment is basically the same as embodiment 3, except that in step (2), the mass ratio of EGaIn micro-nano particles to PVA is 2:1, specifically, 0.2 g of EGaIn micro-nano particles is added to the monomer solution, and a mixed solution is obtained after ultrasonic dispersion.
[0075] Mechanical properties of highly mechanically stable conductive hydrogels with hierarchical structures at different monomer concentrations
[0076] The mechanical properties of the conductive hydrogels with layered structures obtained in Examples 3, 8, 9, 10 and 11 were tested, and the stress-strain curves thereof are shown in FIG. Figure 4 As shown. With the increase of the content ratio of EGaIn micro-nanoparticles, the fracture strain of the conductive hydrogel with a layered structure first increases and then decreases. When the mass ratio of EGaIn micro-nanoparticles to PVA is 1.5, the maximum fracture strain of the conductive hydrogel is 820%. The reason is that EGaIn micro-nanoparticles have a low modulus. The EGaIn micro-nanoparticles located in the PVA polymer layer can coordinate with the hydroxyl groups on the PVA. When the material is deformed by external force, the EGaIn micro-nanoparticles can deform along the tensile direction, which plays a role in stress dissipation. The ductility of the conductive hydrogel with a layered structure is improved. However, with the increase of the content of EGaIn micro-nanoparticles, too many particles will destroy the PVA network, form defects, and reduce the mechanical properties of the PPSLM gel.
[0077] Electrical properties of highly mechanically conductive hydrogels with hierarchical structures at different monomer concentrations
[0078] The electrical properties of the conductive hydrogels with layered structures prepared in Examples 3, 9, 10 and 11 were tested, and the initial resistance graphs thereof are shown in FIG. Figure 6 The corresponding strain resistance diagram is shown in Figure 7 As the content ratio of EGaIn micro-nanoparticles increases, the LM nanoparticle layer at the bottom becomes thicker, so a denser conductive network can be formed when activated, thus achieving lower resistance.
[0079] Test of the relative change rate of resistance of conductive hydrogel with high mechanical properties and hierarchical structure under different operations
[0080] The conductive hydrogel with a layered structure prepared in Example 10 was tested for the relative change rate of resistance under different operations. The test results are as follows: Figure 8 , 9 As shown in Figures 1 and 10. The test results show that when weights of different masses (from 200g to 1000g) are placed on the conductive hydrogel with a layered structure, its relative resistance changes by less than 0.75%, and the conductive hydrogel with a layered structure changes by less than 0.6% after 150 torsion cycle tests. When the conductive hydrogel with a layered structure is subjected to bending tests at different angles, its relative resistance change also maintains a change rate below 0.75%. Therefore, the hydrogel has the performance of maintaining a high stable conductivity under different deformation conditions.
[0081] Application Example 1
[0082] 1. Preparation of ultra-thin wearable capacitive sensors
[0083] The hydrogel layers of two sheets of conductive hydrogel with a layered structure prepared in Example 10 were brought into contact with each other, so that the liquid metal conductive layers of the two sheets of hydrogel were used as the upper and lower electrodes of the sensor respectively, and then packaged with VHB tape to prepare an ultrathin wearable capacitive sensor.
[0084] 2. Strain response test of ultra-thin wearable capacitive sensors
[0085] The strain responses of the ultra-thin wearable capacitive sensor to finger bending, knee bending, and swallowing mode were tested. Fig.11 , 12 As shown in Figures 13 and 13, the results show that the ultrathin wearable capacitive sensor maintains a stable and sensitive response to different strains.
[0086] 3. Stress response test of ultra-thin wearable capacitive sensors
[0087] The ultra-thin wearable capacitive sensor was tested for its response time to a single press. The results are as follows: Fig.14 As shown, the sensor responds quickly and sensitively.
[0088] The ultra-thin wearable capacitive sensor was tested for its response to repeated stress at different pressing times. Fig.15 As shown, the sensor maintains a stable and sensitive response under the same stress.
[0089] The ultra-thin wearable capacitive sensor was tested for its response to repeated stress under different pressures. Fig.16 As shown, the sensor maintains a stable and sensitive response under the same stress.
[0090] Application Example 2
[0091] 1. Preparation of bioelectrode
[0092] The conductive hydrogel with a layered structure prepared in Example 10 can be used as a bioelectrode and attached to the human eye to measure the electrooculogram (EOG) signal; it can also be attached to the human wrist pulse to measure the electrocardiogram (ECG) signal. It has high sensitivity and accuracy.
[0093] 2. EOG signal test of bioelectrode
[0094] The conductive hydrogel with a layered structure prepared in Example 10 was used as a bioelectrode to test the EOG signal. The results are as follows: Fig.17 As shown, the different signal responses when looking left and looking right are shown.
[0095] 3. ECG signal test of bioelectrode
[0096] The ECG signal test of the conductive hydrogel with a layered structure prepared in Example 10 as a bioelectrode is shown in the following results. Fig.18 As shown, different signal responses are shown during normal and after exercise.
Claims
1. A method for preparing a highly stretchable and highly conductive hydrogel having a layered structure, characterized in that: The specific steps include: (1) According to the mass ratio of PEDOT:PSS solution to PVA being 1:1 to 3:1, a 1.0% PEDOT:PSS solution is first added to the PVA solution, and then water is added and mixed and stirred to obtain a monomer solution; (2) Adding EGaIn micro-nanoparticles to PVA at a mass ratio of 0.5 to 1.5:1 into the monomer solution, and obtaining a mixed solution after ultrasonic dispersion; (3) The mixed solution was injected into a mold, heated and cured at 70±5°C for 30-40 min, and then demolded to obtain a highly stretchable and highly conductive hydrogel with a layered structure.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the PVA solution is 10%, and the mass ratio of the PEDOT:PSS solution to the PVA is 2:
1.
3. The preparation method according to claim 1, characterized in that: In step (1), in the monomer solution, the mass ratio of PVA to water is 0.1:1.
494.
4. A highly stretchable and highly conductive hydrogel with a layered structure obtained according to the preparation method of any one of claims 1 to 3.
5. Use of the highly stretchable and highly conductive hydrogel with a layered structure according to claim 4 in the preparation of a flexible wearable capacitive sensor.
6. The use according to claim 5, characterized in that: The specific application method is: two hydrogel layers of the above-mentioned high-stretchability and high-conductivity hydrogel with a layered structure are brought into contact with each other, the conductive layers of the two hydrogels are used as the upper and lower electrodes of the sensor respectively, and then packaged with VHB tape to prepare a flexible wearable capacitive sensor.
7. Use of the highly stretchable and highly conductive hydrogel with a layered structure according to claim 4 in the preparation of a bioelectrode.
Citation Information
Patent Citations
Flexible myoelectric electrode array and preparation method and application thereof
CN114366110A
Super-stretchable dual-network composite conductive hydrogel and preparation method thereof
CN116284862A
Preparation method of LMPP conductive hydrogel, LMPP conductive hydrogel and application of LMPP conductive hydrogel
CN118580528A
3D printed active electronic materials and devices
US20180159037A1
Stretchable electronics and methods of making the same
US20200234842A1